The Influence Of Destination Image and Electronic Word Of Mouth (E-WOM) On Tourist’s Intention To Visit Keranggan Ecotourism Village - Khairani, Nabila; Haris Muchtar, Abdul (SocioHumania: Journal of Social Humanities Studies, 2024)
Tourism refers to a series of travel activities undertaken by individuals or groups from their place of residence to various destinations solely for leisure purposes, excluding work-related or income-generating motives. The tourism industry holds significant importance as it contributes to foreign exchange earnings, facilitates transactions amounting to trillions of rupiah, generates employment opportunities, and fosters product development. This study adopts a quantitative approach, employing a questionnaire administered through Google Forms for data collection. Data analysis is conducted using SPSS version 25. The population size is undetermined, with non-probability sampling employed as the sampling technique. The sample comprises 96 individuals who exhibit an interest in or intend to visit Keranggan ecotourism village, having accessed information about it via social media. The research findings reveal an R-Square value of 0.708, indicating that 70.8% of the variance in visiting interest can be explained by destination image and electronic word of mouth variables. Specifically, the study highlights the significant and positive influence of destination image on visiting interest, as well as the positive impact of electronic word of mouth (e-WOM) on the same